INSTRUMEN KETERAMPILAN SOSIAL BERBASIS OBSERVASI DAN SOSIOMETRI PADA PEMBELAJARAN IPS DI SMP - Eri Purwanti; Edy Purnomo; Pujiati Pujiati (Metafora: Education, Social Sciences and Humanities Journal, 2020)
Instruments of Social Skills Observation and sociometry based on Learning Social studies in junior high school. The purpose of this research is to implement the instruments of social skills of observation and sociometry based on learning in junior high school social studies, analyze the effectiveness of use of instruments of social skills in social studies learning. This study classified as comparative studies with experimental approaches. The method used is a quasi-experimental methods (quasi-experimental design). Sampling was done by cluster random sampling and the sample was 64 students from two different classes. Data collected by questionnaire and observation sheet. Data were analyzed using t-test formula for two large samples to each other do not have a relationship. The results showed: The test results showed that the effectiveness of the instruments of social skills-based observation and sociometry more effective and fit for use.